Anti-dermatophyte activity of the aqueous extracts of Thai medicinal plants - Chaiwaree,S. (2022)
Abstract Medicinal plants have long been prescribed in Thailand for centuries. Different constituents of extracts have been used for treating of various infectious diseases. However, there is even less information available regarding the use in fungal skin infection. In order to assess traditional Thai claims about the therapeutic potential, this study is focused on exploring the anti-dermatophyte property of the plants that are currently used as traditional medicines. The potential of four different plant species were selected for investigate in vitro anti-dermatophyte activity. Ethanolic extracts of Chromolaena odorata (L.), Ageratina adenophora (Spreng.), Eclipta prostrate (Linn.), and Acorus calamus (L.). were analysed for their total phenolic content as well as total flavonoid content and were then subjected to test of their anti-dermatophyte properties using agar well diffusion method. Qualitative flavonoids and phenolics analysis of the extracts showed their biologically active constituents. Among the species examined, the result indicated that most of the extracts demonstrated anti-dermatophyte activity. In particular, A. calamus showed the highest efficacy against test organisms. The experiment confirmed the chemical constituents and efficacy of some selected plants and provides a scientific confirmation of the use of Thai plants in traditional medicine for fungal skin infections.